Discontinuous phasor model of an inductive power transfer system - Scarciotti,G (IEEE, 2017)
Recently, a new discontinuous phasor transform has been introduced. The discontinuous phasor can represent the steady-state quantities of electrical circuits powered by discontinuous sources (e.g. square waves) without approximations. In this paper we provide a discontinuous phasor model of a two-coil inductive power transfer system. We validate this model studying the relation between the maximum power dissipated by the load and the frequency of the square wave. The simulations show that the new model correctly describes the steady-state behavior of the circuit for any quality factor and for any frequency.